2021
DOI: 10.1002/jsfa.11550
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the effect of fatty acid composition on the texture of French fries

Abstract: BACKGROUND Several researchers have reported that the texture of fries is affected by the fatty acid composition of oil, although the mechanism of this effect is not clear. In this regard, fries were fried in refined rapeseed oil and fully hydrogenated rapeseed oil with diverse proportions (0%, 20%, 40%, 60%, 80% and 100%) and were analyzed based on the content of moisture and oil, texture, thermal properties, crystalline properties and microstructure. RESULTS The outcomes presented that fries fried in fully h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…The dense crust that formed at early stage of frying inhibited the migration of internal moisture and subsequently increased the internal pressure and induce large holes and cracks 42 . These large holes would allow more oil to penetrate into the structure, thus increasing oil absorption in fried ginkgo seeds 43 . However, the fried samples with ultrasonic treatmen were observed to have a coarser morphology and smaller holes, with diameters in the range 41–62 μm, and the starch was fully gelatinized, lost its original granular structure and filled in the entire cellular structure after dehydration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dense crust that formed at early stage of frying inhibited the migration of internal moisture and subsequently increased the internal pressure and induce large holes and cracks 42 . These large holes would allow more oil to penetrate into the structure, thus increasing oil absorption in fried ginkgo seeds 43 . However, the fried samples with ultrasonic treatmen were observed to have a coarser morphology and smaller holes, with diameters in the range 41–62 μm, and the starch was fully gelatinized, lost its original granular structure and filled in the entire cellular structure after dehydration.…”
Section: Resultsmentioning
confidence: 99%
“…42 These large holes would allow more oil to penetrate into the structure, thus increasing oil absorption in fried ginkgo seeds. 43 However, the fried samples with ultrasonic treatmen were observed to have a coarser morphology and smaller holes, with diameters in the range 41-62 μm, and the starch was fully gelatinized, lost its original granular structure and filled in the entire cellular structure after dehydration. The gelatinization enthalpy of starch was significantly reduced after ultrasonic pretreatment and the permeability of cell structure was improved, which accelerated crust formation and increased surface roughness.…”
Section: Crust Observation and Characterizationmentioning
confidence: 99%
“…This was related to the uneven distribution of oil and moisture in the crust and core of the French fries. Li et al 24 found that the oil in French fries was mainly distributed in the crust and the moisture was mainly concentrated in the core. Therefore, the hydrophobic PAH4-d12 mainly migrated into the crust instead of the core.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The microcosmic morphology was recorded using an SEM analyzer (Regulus 8100; Hitachi Ltd., Tokyo, Japan) at an accelerating voltage of 3 kV [ 23 ]. The samples were placed on a metal stub with double-sided adhesive tape and sputter-coated with gold in a vacuum sputter coater to make the samples conductive.…”
Section: Methodsmentioning
confidence: 99%